ECONOMIC EFFICIENCY OF IMPLEMENTING NEW TECHNIQUES AND ADVANCED TECHNOLOGIES IN AGRIBUSINESS - Turdimuratova Aziza Alisherovna (Scholar Express Journal, 2022)
Digitalization has covered all areas of the social and economic life of society. This trend is a key factor in the development of the agricultural industry, since digitalization is today the main driver that increases the productivity and efficiency of the production process in the agricultural sector. Achieving growth in agribusiness profitability requires full use of innovative technologies. In this paper, we want to consider the concept of introducing new technologies and their effectiveness in agriculture, in particular in crop production
Keywords: agribusiness; accounting; digital technologies; new technology